INTELLECTUAL CAPITAL, INVESTMENT DECISIONS DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Ferina Octavia Samosir; Yuliani Almalita (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The aims of this research to obtain empirical evidence about the effect of intellectual capital, intellectual capital disclosure, corporate financial performance, investment decisions, funding decisions, dividend policy, liquidity to firm value on non-financial companies in Indonesia Stock Exchange (IDX) during the research period 2019-2021. Sample selection method that used purposive sampling and there were 71 non-financial companies met by criteria, resulting 184 data are taken as sample. Data were analyzed by used the multiple linear regression techniques. The results of this research showed corporate financial performance, investment decision, funding decisions, dividend policy, and liquidity has a effect on firm value. Meanwhile, intellectual capital and intellectual capital disclosure have no effect on firm value.